Implementasi Pedoman Etika Akademik Digital dalam Meningkatkan Disiplin Belajar Siswa Sekolah Menengah: Penelitian - Herlinawati; M. Firdaun; Dian Nasrah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The digital transformation of education has expanded academic interactions while simultaneously introducing new challenges related to student ethics and discipline in learning processes. This community engagement program aims to address these issues through the development and implementation of a Digital Academic Ethics Guideline at SMA Negeri 2 Tambang. The program was conducted in three main phases: teacher training, participatory document development, and formative evaluation of program effectiveness. Pre-test and post-test results demonstrated a significant increase in teachers’ understanding of digital academic ethics, including communication (+27%), ethical use of technology (+27%), and moral responsibility in online learning (+26%). The guideline document was collaboratively formulated based on training outcomes, literature review, and contextual school needs. A formative evaluation involving 34 teachers showed high scores in material relevance (4.71), professional benefit (4.68), and implementation readiness (4.74), indicating the program’s success in fostering ethical awareness and disciplined academic behavior. This article argues that digital ethics–based approaches can serve as strategic instruments in cultivating a responsible, adaptive, and sustainable academic culture at the secondary school level.